Aberration-corrected transmission electron microscopy of a non-graphitizing carbon - Allen, CS; Ghamouss, F; Boujibar, O; Harris, PJF (Royal Society, 2022)
Non-graphitizing carbons (NGCs) are an important class of solid carbons which cannot be converted into graphite by high-temperature heat treatment. They include commercially valuable materials such as activated carbon and glassy carbon. These carbons have been intensively studied for decades, but there is still no agreement about their detailed atomic structure, or the reasons for their resistance to graphitization. The first models for graphitizing and NGCs were proposed by Rosalind Franklin in the early 1950s, and while these are broadly correct, they are incomplete. Many alternative models of NGCs have been put forward since Franklin's time, but none has received universal acceptance. Diffraction and spectroscopic techniques can provide important insights into the nature of these carbons, but only direct microscopic imaging can reveal their true atomic structure. Here, we apply aberration-corrected transmission electron microscopy to an activated carbon prepared from waste biomass and present evidence for the presence of pentagonal and heptagonal carbon rings. This provides support for a model of the structure of NGC made up of curved fragments in which non-hexagonal rings are dispersed randomly throughout hexagonal networks.